PROTOTYPE PEMANFAATAN WIRELESS SENSOR NETWORK MENGGUNAKAN KOMUNIKASI WIRELESS ZIGBEE UNTUK MONITORING POWER QUALITY PADA PEMBANGKIT PLTMH - Rachmad Ikhsan; Inzar Salfikar (J-Innovation, 2015)
The continued development of industrial technology at this point that leads to the field of moderninformation technologies so as to facilitate the work of man. The use of electrical energy continues toincrease over time, causing consumers want to know the quality of electrical energy consumed, resultingfrom the demand for electrical energy monitoring needs to be done in this case concerns the quality ofelectric power generated from a mini-hydro power plant (PLTMH). In this study, we will design andsimulate the process parameters of electrical energy to be monitored, in the form of voltage, current,frequency and different phase that will be on all four of these parameters will be used as a reference if thequality of power (power quality) of a plant is good or no. To obtain the data we use multiple sensorsnamely, voltage sensor, current sensor and sensor using a frequency of zero crossing detector. Dataparameters of electrical energy on each sensor node is transmitted wirelessly using XBee RF modules areintegrated with zigbee protocol to the gateway. On the side of the gateway will connect via CDMA andsend packets of data - the data packets to the web database. Consumers can access the data - the data viathe mobile phone network to a web-connected database. On the web will be shown the data - the dataparameter values of the electrical energy. So that consumers can see the parameters of electrical energythat is needed is good or not.